Geographical patterns of excess mortality in Spain explained by two indices of deprivation - Benach, J. (BMJ Group, 1999)
STUDY OBJECTIVE: To analyse the geographical patterns and the magnitude of the association between deprivation and mortality in Spain. To estimate the excess of mortality in more deprived areas of the country by region. DESIGN: Cross sectional ecological study using 1991 census variables and mortality data for 1987-1992. SETTING: 2220 small areas in Spain. MAIN RESULTS: A geographical gradient from north east to south west was shown by both mortality and deprivation levels in Spain. Two dimensions of deprivation (that is, Index 1 and Index 2) obtained by exploratory factor analysis using four census indicators were found to predict mortality: mortality over 65 years of age was more associated with Index 1, while mortality under 65 years of age was more associated with Index 2. Excess mortality in the most deprived areas accounted for about 35,000 deaths. CONCLUSIONS: Two indices of deprivation strongly predict mortality in two age groups. Excess number of deaths in the most deprived geographical areas account for 10% of total number of deaths annually. In Spain there is great potential for reducing mortality if the excess risk in more deprived areas fell to the level of the most affluent areas.